2008
DOI: 10.1136/hrt.2007.118471
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of epicardial adipose tissue by echocardiography to coronary artery disease

Abstract: These results suggest that EAT may reflect the amount of visceral fat, which is associated with insulin resistance and inflammation. The echocardiographic measurement of EAT may provide additional information for assessing CAD risk and predicting the extent and activity of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
223
2
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(253 citation statements)
references
References 17 publications
(22 reference statements)
18
223
2
10
Order By: Relevance
“…In this study, we used the echocardiographic epicardial fat as marker of visceral adiposity, as previous studies from our group (7,12,14,20) and also from other authors (8,21) showed.…”
Section: © 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used the echocardiographic epicardial fat as marker of visceral adiposity, as previous studies from our group (7,12,14,20) and also from other authors (8,21) showed.…”
Section: © 2008mentioning
confidence: 99%
“…We showed that echocardiographic assessment of epicardial adipose tissue can serve as a new index of cardiac and visceral adiposity. We also previously demonstrated that epicardial fat is clinically correlated with magnetic resonance imaging abdominal visceral adiposity (7), coronary artery disease (8,9), atherosclerosis (10,11), and major anthropometric and metabolic predictors of increased cardiometabolic risk (12)(13)(14). Emerging evidences suggest that epicardial fat may act as therapeutic target during therapeutic interventions modulating the adipose tissue (15).…”
Section: Introductionmentioning
confidence: 99%
“…It is a metabolically active organ that generates various bioactive molecules that are directly involved in inflammation and known to modulate vascular and myocardial functions, including adiponectin, tumor necrosis factor-(TNF-), interleukin-6 (IL-6), and monocyte chemoattractant protein-1 (MCP-1) 6,7) . EAT thickness measured with transthoracic echocardiography (TTE) has been demonstrated to have a strong correlation with abdominal adiposity measured with computed tomography (CT) or magnetic resonance imaging (MRI) 5,8,9) .…”
Section: Study Protocolmentioning
confidence: 99%
“…EAT, measured with either TTE or CT, has also been associated with the presence and increased severity of coronary artery disease (CAD), and the presence of coronary calcification in a large number of studies 8,12) . Furthermore, EAT thickness has been demonstrated to be a stronger predictor for CAD than any other visceral adipose tissue located in the body 13) .…”
Section: Study Protocolmentioning
confidence: 99%
“…По данным различных исследований лица с коро-нарным атеросклерозом отличаются большей вели-чиной ТЭЖ по сравнению с пациентами с неизме-ненными коронарными артериями [27], при этом величина показателя взаимосвязана с тяжестью ИБС, определяемой по индексу Gensini [28,29]. У асим-птомных пациентов толщина и объем ЭЖТ незави-симо ассоциированы с кальцификацией коронарных сосудов, оцениваемой по коронарному кальциевому индексу, а также с тяжестью поражения коронарного русла по данным коронароангиографии [30][31][32].…”
Section: эпикардиальная жировая ткань: основные характеристики и метоunclassified